Hydro-chemical characteristics and water environment of the surface water and shallow groundwater in the North of Yellow River Delta, China - Wang, Kui-Feng; Liu, Ni-Na; Xia, Jiang-Bao; Chu, Xiao-Jing; Xu, Shu-Jian; Zhang, Tai-Ping; Hu, Ge; Liu, Yang; Zhang, Hong-Jun; Xu, Yan (Tecnología y ciencias del agua, 2023)
The present study envisaged the dynamic monitoring and study of the hydrochemistry of the surface water and shallow groundwater in the northern part of the Yellow River Delta, China. Analysis of the surface water and shallow groundwater revealed that the shallow groundwater exhibited in two forms: precipitation evaporation type and hydrological type, and the latter was obviously affected by the dynamic water level of the Yellow River. The surface water and shallow groundwater exhibited a higher degree of mineralization. Cations of Mg2+, Na+ and K+ and anions of Cl- and SO42- were the main ion components of the total dissolved solids. The hydro-chemical type of shallow groundwater was Cl-Na·K that was a typical seawater or brine form. The water chemical type of surface water changed to Cl·SO4-Na·K·Ca due to the industrial, agricultural and urban pollution. The overall quality of surface water was poor, and the main pollution indexes were found to be present, except for cyanide. The levels of COD and fluorine exceeded the standard values in the surface water. The groundwater quality was poor, since most of the pollutants were detected, except for cyanide and volatile phenol. Eight indexes exceeded the groundwater quality standard levels including Cl-, Na+, total hardness, COD, NH4+, Hg, As, NO3-, Cl- and Na+. The pollution of the surface water and shallow groundwater was mainly caused by the discharge of the wastewater from the petroleum; chemical industry and brine enterprises; agricultural non-point source pollution; leakage of septic tanks and sewage pipes in urban and rural areas, and rainwater leaching from the garbage piles. In order to improve the water quality, the sewage control and management needs be optimised, and the industrial layout should be reconsidered.